Strategi Pemimpin Dalam Pengelolaan Perubahan Organisasi - Wahyudi, Ilham; Sindo, Pablo; Hasri, Salfen; Sohiron, Sohiron (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2025)
This article aims to identify and analyze effective leadership strategies in change management. This study uses a literature review method with a qualitative approach, aimed at gaining an in-depth understanding of the phenomenon of change within organizations. The researcher analyzes various relevant sources of literature, including books, journals, and articles related to leadership theories and change management. The main findings indicate that effective and transparent communication, trust and commitment building, capacity training and development, as well as monitoring and evaluation are key strategies in managing change. Clear and open communication helps reduce uncertainty, while building trust and commitment enhances collaboration and team performance. Additionally, appropriate training and change process evaluation ensure that organizational members are prepared to adapt, and the changes made have a positive impact. This study concludes that resilient and adaptive leaders, by implementing these strategies, can lead effective change within organizations.